2016
DOI: 10.1161/circgenetics.116.001515
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Nonfermenting-Related Kinase Enzyme–Mediated Rho-Associated Kinase Signaling is Responsible for Cardiac Function

Abstract: Background Cardiac metabolism is critical for the functioning of the heart, and disturbance in this homeostasis is likely to influence cardiac disorders or cardiomyopathy. Our lab has previously shown that sucrose non-fermenting related kinase (SNRK) enzyme, which belongs to the AMP-activated kinase (AMPK) family, was essential for cardiac metabolism in mammals. Snrk global homozygous knockout (KO) mice die at postnatal day 0, and conditional deletion of Snrk in cardiomyocytes (Snrk cmcKO) leads to cardiac fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…To date, the role of SNRK in energy homeostasis has been reported only for the heart. SNRK is essential for maintaining the function of the heart; lethality has been observed in cardiomyocyte-specific SNRK knockout mice between 8 and 10 months of age, including those with heterozygous loss of SNRK in cardiomyocytes (25,27). However, findings are inconsistent concerning the effect of SNRK on lipid metabolism in the heart (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the role of SNRK in energy homeostasis has been reported only for the heart. SNRK is essential for maintaining the function of the heart; lethality has been observed in cardiomyocyte-specific SNRK knockout mice between 8 and 10 months of age, including those with heterozygous loss of SNRK in cardiomyocytes (25,27). However, findings are inconsistent concerning the effect of SNRK on lipid metabolism in the heart (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, findings are inconsistent concerning the effect of SNRK on lipid metabolism in the heart (25,26). Cossette and colleagues (25,27) reported decreased fatty acid oxidation when SNRK expression was reduced in cardiomyocytes, with reductions of phospho-acetyl-CoA-carboxylase, phospho-AMPK, and Rhoassociated kinase, whereas Rines et al (26) reported increased fatty acid oxidation in hearts of SNRK knockout mice and decreased fatty acid oxidation with SNRK overexpression. Despite a protective effect of SNRK against ischemia/reperfusion, SNRK functions seem complex and may involve changes in mitochondria efficiency through decreasing UCP3 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac metabolism Regulates cardiac metabolism through phospho-acetyl-CoA carboxylase (ACC) and phospho-AMPK signaling pathway [15] Cardiac functioning Regulates Rho-associated kinase (ROCK) signaling pathway and mitochondrial efficiency through uncoupling protein 3 (UCP3) and mitochondrial uncoupling [13,16] Cardiac inflammation Represses inflammation by regulates NF-κB phosphorylation [14] Adipose system Adipocyte glucose metabolism Regulates insulin signaling mediated glucose uptake through PPP2R5D and Akt phosphorylation [17] Adipocyte inflammation Represses inflammation in white adipose tissue through JNK and IKKβ pathways [19] Adipose thermogenesis Represses WAT inflammation and regulate BAT thermogenesis through UCP1 and PGC1α [18] Vascular system Vasculogenesis Maintain angioblast populations and control angioblast numbers in embryonic vascular development through DUSP5 [20] Angiogenesis Promote endothelial angiogenesis by activating ITGB1 (β1 integrin)mediated endothelial cell migration [21] Renal system Kidney inflammation Represses inflammation by directly interacting with NF-κB phosphorylation [22] Colorectal system Colon cancer Inhibits colon cancer cell proliferation through upregulation of calcyclin-binding protein (CacyBP) and β-catenin degradation [12] Ovarian system Ovarian cancer Omental adipocytes transport fatty acids for rapid growth, progression, and metastasis of ovarian cancer cells [23] Neuronal system Neuron apoptosis Regulates low K + -induced apoptosis in cerebral neurons [24] Table 1. The role of SNRK in various cellular systems is shown SNRK: sucrose nonfermenting 1-related kinase; AMPK: AMP-activated protein kinase; NF-κB: nuclear factor kappa-light-chain-enhancer of activated B cells; PPP2R5D: serine/threonine-protein phosphatase 2A 56 kDa regulatory subunit delta isoform; Akt: protein kinase-B; JNK: Jun N-terminal kinase; IKKβ: IκB kinase β subunit; WAT: white adipose tissue; BAT: brown adipose tissue; PGC1α: peroxisome proliferator-activated receptor γ isoform α; DUSP5: dual-specificity phosphatase 5; ITGB1: Integrin beta-1…”
Section: Cardiac Systemmentioning
confidence: 99%
“…Unlike many AMPKs, SNRK does not require an additional stimulus for activation such as increased AMP:ATP [12] ratio within a cell. SNRK also phosphorylates several proteins including Rho-associated kinase (ROCK) [12][13][14][15][16][17][18][19] . Thus, SNRK regulation and its associated signaling partners and pathways are emerging areas of research.…”
Section: Introductionmentioning
confidence: 99%